Konsep Khalifah dalam Membentuk Pribadi yang Mulia - Bina Prima Panggayuh; Zahra Tian Nur Alifa; Thalita Hanasyifa Prasetya; Intan Mariska; Jaffan Faiz Ijjudan (Advances In Education Journal, 2025)
The Islamic concept of khalifah positions humans as earth's leaders and stewards, responsible for maintaining balance and moral values. This study analyzes how understanding khalifah contributes to noble character formation. Employing a literature review of primary sources like the Qur’an and Hadith, plus scholarly works on Islamic ethics and character education, the findings reveal that khalifah fosters essential values: responsibility, trustworthiness, honesty, justice, social care, and spiritual awareness. Internalizing these shapes morally upright personalities in personal, educational, and social contexts. A comprehensive grasp of the khalifah role heightens ethical awareness and promotes positive societal contributions. Ultimately, khalifah transcends theology, serving as a foundational framework for character development that produces individuals excelling intellectually, morally, and spiritually.